THE APPLICATION OF Trichoderma viride STRAIN FRP 3 FOR BIODEGRADATION OF GLYPHOSATE HERBICIDE IN CONTAMINATED LAND - Arfarita, Novi; Djuhari, Djuhari; Prasetya, Budi; Imai, Tsuyoshi (AGRIVITA, Journal of Agricultural Science, 2016)
In this current study, we observed Trichoderma viride strain FRP3 capability for biodegradation of glyphosate on contaminated land in Indonesia. There were two blank plots that have been involved as representatives of indigenous fungal, that prepared as control (non-contaminated soil) and P1 (GP-contaminated soil) while the treatments were represented by two plots.  Plot 2 (P2) was introduced with conidia suspension of Trichoderma viride strain FRP3 one time application, and plot 3 (P3) was introduced with conidia suspension of Trichoderma viride FRP3 two time applications. At the end of observation, the CFU of two times application was the highest with CFU of 15.97 x 106 gr-1 soil. The CFU of P3 was corresponding to 45% higher than P2 (8.83 x 106 gr-1 soil). The CFU of GP-contaminated soil without conidia suspension application had 0.66 x 106 gr-1soils, only 0.7% and 0.4% corresponding to P2 and P3, respectively. Direct indicator of glyphosate degradation was determined using GC analysis. Within 7 days after Trichoderma viride FRP3 was introduced, glyphosate content of treated soil decreased. This fungal strain provided 48% (P2) and 70% (P3) of glyphosate degradation higher than indigenous soil microbial community (P1) within 28 days of application.